Advancements in hazardous gases detection: Using dual structures of photonic crystal fiber-based sensor - Pratishtha Pandey; Sapana Yadav; Adarsh Chandra Mishra; D.K. Dwivedi; Pooja Lohia; R.K. Yadav; Upendra Kulshrestha; Vipin Kumar; Prabhu Paramasivam; R. Bousbih; M. Khalid Hossain (Sensing and Bio-Sensing Research)
This paper presents a comparative analysis of two distinct nonlinear elliptical hollow-core photonic crystal fiber (PCF) based sensors designed for the detection of three gaseous analytes, namely CCl4 (n = 1.461), SnCl4 (n = 1.5086) and C10H16 (n = 1.472). A comprehensive examination is conducted across a wide wavelength range (1.2 μm–2.6 μm). In order to enhance both the fabrication tolerance and sensing performance of the proposed sensors, investigations have been conducted on the diameter of circular and elliptical-shaped air holes, as well as the dimensions of struts and the core size. Silica works as background material for both the sensors. The sensing parameters including relative sensitivity, effective area, birefringence, and dispersion, have been obtained for two different sensors proposed for evaluation. The numerical investigation employs the finite element method based on Comsol Multiphysics. When comparing both sensors, sensor design-2 stands out with an impressive nonlinear coefficient value of 15.470 W−1Km−1, a higher relative sensitivity of 98.386 %, enhanced effective area of 1.134× 10−11 m2, comparable effective refractive index of 1.496 and significant birefringence −4.701 × 10−5, along with low confinement loss for SnCl4 followed by CCl4 and C10H16 at 1.2 μm operating wavelength, owing to its higher refractive index compared to sensor design-1 for same sensing analyte. The designed model holds potential applications in sensing, bio-sensing research, and related fields.